Prognostic factors and health-related quality of life in ocular myasthenia gravis (OMG). (1st June 2014) - Ariatti, Alessandra; Stefani, Marina; Miceli, Pietro; Benuzzi, Francesca; Galassi, Giuliana
<x xml:space="preserve">Abstract</x> We evaluate the factors predictive of prognosis in 91 Caucasian patients affected by ocular myasthenia gravis (OMG), followed at our Institution during an observational time, ranging from 12 to 240 months. The Myasthenia Gravis Foundation of America (MGFA) clinical classification was used to grade the disease severity. We considered as outcome measures the variation in two subscores, ocular (O-QMG) and nonocular (NO-QMG); the last one reflected bulbar, neck, extremity functions. None of the independent variables evaluated for association with the outcome, as age of onset, type of therapy, length of interval between first and last examinations, and presence of antibodies to acetylcholine receptors (AChR-Abs) significantly affected the evolution of O-QMG and of NO-QMG. Health-related quality of life (HRQol) was assessed in 63 patients. Variations of diplopia or ptosis did not affect significantly physical (PCS) or mental composite subscores (MCS) of the Short-Form Health Survey (SF-36). Human leukocyte antigen (HLA) genotyping was studied to explore whether HLA class I and II allelic distribution differed among MG patients and controls. None of the studied HLA alleles significantly differed between OMG patients and controls. Similarly, none of the alleles with frequencies higher than 15% either in OMG patients or in controls was significantly associated, after Bonferroni correction, with the presence or absence of anti-AChR-Abs in serum.